Integration of Flipped Learning and Project-based Learning: Analysis of Combined Effects on Students' Academic Performance - Hukom, Julham; Irfan (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2025)
This study aims to comprehensively evaluate the effectiveness of the Flipped Learning model integrated with Project-Based Learning (FL-PjBL) on student learning outcomes through a meta-analysis approach. A total of twelve studies (k = 13) that met the inclusion criteria were analyzed using a random-effects model to accommodate variations between studies. The results of the meta-analysis showed that the FL-PjBL model had a significant positive effect on improving student learning outcomes, with an effect size (d) value of 1.22 and a significance of p < 0.01, which is included in the large effect category. However, the high level of heterogeneity (I² = 83.64%) indicated substantial variation between studies. Therefore, further research is recommended to investigate moderator variables such as educational level, subject area, intervention duration, and the quality of technology integration and project design in learning.